La expresión del futuro en las variedades oral y escrita del español de Uruguay - Bértola, Cecilia; Taibo, Marcelo (Borealis – An International Journal of Hispanic Linguistics, 2023)
In this article, we analyze the differences in the distribution and interpretation of the synthetic future [-RÁ] and the periphrastic future [IR + a + Inf] in the oral and written records of Uruguayan Spanish. The quantitative and qualitative analysis of two corpora -oral and written- shows that the written language maintains the preference of [-RÁ] to refer to the future while in orality it is pronounced by [IR + a + Inf] and [-RÁ] is used solely as an uncertainty operator. The type of sentences in which [-RÁ] appears in orality (independent and subordinates with complete left periphery) is an indication that this operator is interpreted at the extrapropositional level of the SFuerza projection. In the geographical area studied, the two ways to refer to the future coexist, which leads us to conclude that there are two grammars, one associated with the written language and the other with the oral language.